Imine bond connected two-dimensional covalent organic framework material and application thereof in lithium ion battery with 110000 cycle stability

By using two-dimensional covalent organic frame materials connected by imine bonds in lithium-ion batteries, the shortcomings of lithium-ion battery electrode materials in cyclic stability and rate performance are solved, and ultra-long cycle stability and high electrochemical performance are achieved. , suitable for efficient applications of lithium-ion batteries.

CN119119460AActive Publication Date: 2024-12-13UNIV OF SCI & TECH BEIJING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411261744.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrode materials have not yet met the high requirements in energy storage systems, renewable energy smart grids and micro sensors in terms of cycle stability and rate performance, especially for ultra-long cycle stability and rate performance. There are still challenges in realizing it.

Method used

Two-dimensional covalent organic frame materials connected with imine bonds are formed through specific synthesis steps and catalysts to form materials with high crystallinity and hierarchical porous structures for the positive electrode of lithium-ion batteries, enhancing their redox active sites and Ion transport capability.

Benefits of technology

The 110,000-turn ultra-long cycle stability and high specific capacity, energy density and power density of lithium-ion batteries at fast current density have been achieved, which significantly improves the cycling performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119460A_ABST
    Figure CN119119460A_ABST
Patent Text Reader

Abstract

The invention discloses an imine bond connected two-dimensional covalent organic framework material, the structural formula of the covalent organic framework material is # imgabs0 #, and an electrode material prepared from the covalent organic framework material has ultra-long cycle stability and is suitable for a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic battery materials, and specifically relates to an imine bond-connected two-dimensional covalent organic framework material and its application in lithium-ion batteries with 110,000 cycles of cycle stability. Background Art

[0002] As an indispensable energy supply device, lithium-ion batteries have a huge impact on our daily lives. Therefore, designing and synthesizing new battery materials to improve their specific capacity, rate performance and cycle stability has become a hot topic of research. + Compared with inorganic electrodes with intercalation processes, organic electrodes based on simple redox reactions have relatively high specific capacities and can occur in a short time. Therefore, organic electrode materials are considered to be competitive candidates for the next generation of lithium-ion batteries due to their high capacity and fast charging characteristics, and have received widespread attention from countries around the world. However, organic electrode materials based on small molecules have high solubility in organic electrolytes, which will lead to poor cycling stability of the battery. It is a feasible approach to improve the cycling stability of organic electrode lithium-ion batteries by exploring the synthesis of electrode materials based on insoluble polymers.

[0003] Covalent organic frameworks (COFs) are an emerging class of ordered crystalline and porous organic polymers constructed from modular organic building blocks through strong covalent bonds. In addition to applications in gas separation and storage, energy conversion, sensors, semiconductors, catalysis, and proton conduction, COFs with modular structures and designable redox-active units have great potential for battery electrode material applications due to their enhanced chemical / thermal stability associated with strong covalent interactions. Compared with organic small molecules, the advantages of COFs include their rich redox-active functional groups for improving the energy storage capacity of batteries, permanent porosity and tunable pore size for enhanced ion transport, and stable crystalline chemical structure for improving battery cycling stability. Various redox-active organic building blocks, such as anhydrides, quinones, phenazine, and azo, have been used to construct COFs materials as organic electrodes.

[0004] However, the existing COFs electrode materials are far from meeting the high requirements for practical lithium-ion battery electrode materials in fields such as energy storage systems, renewable energy smart grids and microsensors, that is, they must have high rate performance and ultra-long cycle stability. Obviously, due to the long service life and large capacity of lithium batteries used in the above fields, even a moderate improvement in cycle stability is of great significance for significantly reducing costs and saving energy. Studies have shown that improving and increasing the accessibility of COFs redox active sites can improve the cycle stability of lithium-ion battery electrodes. At present, despite many experiments through molecular building block design and mesoscopic scale porous structure construction, the careful preparation of COFs-based lithium-ion battery electrodes with ultra-long cycle stability has not yet been achieved. Summary of the invention

[0005] The purpose of the present invention is to provide an imine bond-connected two-dimensional covalent organic framework material and its application in lithium-ion batteries with 110,000 cycles of cycle stability, aiming to solve the problem pointed out in the background technology that lithium-ion battery electrode materials must have high rate performance and ultra-long cycle stability.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] An imine bond-connected two-dimensional covalent organic framework material, the structural formula of the covalent organic framework material is:

[0008]

[0009] Furthermore, the preparation method of the covalent organic framework material comprises the following steps:

[0010] Step 1: Add 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolin[2,3-b]acridine-7,14-dione and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine to an o-dichlorobenzene / n-butanol solution and disperse by ultrasonication;

[0011] Step 2: Add the catalyst and disperse by ultrasonic again to form a uniform system;

[0012] Step 3, subjecting the system to liquid nitrogen freezing and vacuum degassing treatment;

[0013] Step 4: Use an alcohol burner to seal the tube under vacuum conditions;

[0014] Step 5: react at 120 degrees for 72 hours to obtain a crude product;

[0015] Step 6: Wash the crude product with N,N-dimethylformamide and acetone in sequence, filter it, and dry it in vacuum to obtain a two-dimensional covalent organic framework material.

[0016] Furthermore, in the o-dichlorobenzene / n-butanol solution described in step 1, the volume ratio of o-dichlorobenzene to n-butanol is 2:8.

[0017] Furthermore, the liquid nitrogen freezing and vacuum degassing treatment in step three is performed at least three times.

[0018] Furthermore, the concentration of the catalyst in step 2 is 6 mol / L acetic acid.

[0019] Further, the structural formula of the 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolin[2,3-b]acridine-7,14-dione is as follows:

[0020]

[0021] Further, the structural formula of the N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine is as follows:

[0022]

[0023] Furthermore, the reaction formula of the preparation method of the covalent organic framework material is as follows:

[0024]

[0025] An electrode material comprising the imine bond-connected two-dimensional covalent organic framework material according to any one of claims 1 to 8.

[0026] Further, the application of electrode materials in lithium-ion batteries.

[0027] Due to the adoption of the above structure, the present invention has the following technical advances compared with the prior art:

[0028] The covalent organic framework material powder X-ray diffraction and electron microscopy characterization of the present invention show that the covalent organic framework material has high crystallinity and a double-pore kgm topological structure; N 2 The adsorption-desorption isotherms show that it has hierarchical porosity, with micropore size of about 1.3 nm and mesopore size of about 3.4 nm; the lithium-ion battery cathode prepared by the covalent organic framework material has a stable modular structure and hierarchical micro / mesopore characteristics, allowing the Li in the organic electrolyte to + and PF 6 - Ions fully enter the active center; coupled with its abundant bipolar redox active sites, the lithium-ion battery can -1 145mA hg -1 Specific capacity, 390Wh kg-1 The energy density is 1352W kg -1 Power density and excellent rate performance (10Ag -1 100mA hg -1 Capacity, 231Wh kg -1 The energy density and 23760Wkg -1 power density); in particular, this cathode has a power density of 10000mA g -1 After running for 150 days at a fast current density, it exhibited an ultra-long cycle stability of 110,000 cycles and a capacity retention rate of approximately 100%.

[0029] In summary, the electrode material prepared by the covalent organic framework material in the present invention has ultra-long cycle stability and is suitable for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0031] In the attached picture:

[0032] Figure 1 This is an infrared spectrum of the covalent organic framework material of the present invention;

[0033] Figure 2 The covalent organic framework material of the present invention 13 C CP / MAS NMR spectrum;

[0034] Figure 3 is the XRD pattern of the covalent organic framework material of the present invention;

[0035] Figure 4 A nitrogen adsorption and desorption diagram of the covalent organic framework material of the present invention;

[0036] Figure 5 The cycling performance of lithium-ion batteries assembled with the covalent organic framework material of the present invention is characterized. DETAILED DESCRIPTION

[0037] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0038] Example A two-dimensional covalent organic framework material connected by an imine bond and its application in a lithium-ion battery with a cycle stability of 110,000 cycles

[0039] This embodiment discloses an imine bond-connected two-dimensional covalent organic framework material, such as Figure 1As shown, the covalent organic framework material (QT-COF) is composed of repeating units, each structural unit is connected by an imine bond, and has the general characteristics of a crystal. The covalent organic framework material is formed by polymerizing 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolin[2,3-b]acridine-7,14-dione (QA-PCH) and N,N,N',N'-tetrakis(p-aminophenyl)p-phenylenediammonium (TPPD). The spatial symmetry of the covalent organic framework material is P 321 , the topological type is kgm topology; the structural formula of the covalent organic framework material is as follows: The structural formula of 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolinolato[2,3-b]acridine-7,14-dione is as follows: The structural formula of N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediammonium is as follows:

[0040] The N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine, electrolyte, and porous Celgard 2400 separator used can all be purchased commercially.

[0041] The preparation method of the covalent organic framework material comprises the following steps:

[0042] Step 1: Fill a Pyrex tube with 20.78 mg of 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolinolato[2,3-b]acridine-7,14-dione, 7.1 mg of N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine, 0.2 ml of o-dichlorobenzene and 0.8 ml of n-butanol, and place the Pyrex tube in an ultrasonic generator for ultrasonic treatment;

[0043] Step 2: Add 0.1 ml of 6M / L acetic acid into the Pyrex tube, using acetic acid as a catalyst, and then place the Pyrex tube into an ultrasonic generator for 30 minutes to form a system;

[0044] Step 3, freezing the ultrasonically treated Pyrex tube in liquid nitrogen, and vacuum degassing the frozen Pyrex tube and thawing it to room temperature; the freezing, vacuum degassing and thawing to room temperature process are repeated three times;

[0045] Step 4: Under vacuum conditions, use the flame of an alcohol burner to seal the Pyrex tube to a length of 15 cm;

[0046] Step 5: react at 120 degrees for 72 hours to produce a reddish brown precipitate, and separate the solid by centrifugation to obtain a crude product;

[0047] Step 6: Wash the crude product three times with N,N-dimethylformamide and acetone respectively, collect the product by suction filtration, and vacuum dry it at 80 degrees for 12 hours to obtain 18.7 mg of covalent organic framework material with a yield of 67.1%.

[0048] The reaction formula of the preparation method of the covalent organic framework material is as follows:

[0049]

[0050] Chemical composition, structure determination and crystallinity of covalent organic frameworks

[0051] Using infrared spectroscopy and 13 C solid-state nuclear magnetic resonance was used to analyze the chemical composition of the covalent organic framework materials, and X-ray diffraction technology was used to characterize the structure of the covalent organic framework materials.

[0052] FT-IR spectrum shows that the covalent organic framework material (QT-COF) has the following peaks at 1709, 1325 and 1631 cm -1 Strong vibration bands appeared at 2850-2960 cm-1 and 3200-3500 cm-2, corresponding to the C=O group of QA, the CN unit of TPPDA and the characteristic C=N unit, respectively. -1 The vibration peaks at 1 and 2 disappeared, belonging to the initial aliphatic stretching vibration band of QA and the NH stretching vibration band of TPPDA, respectively, proving that the full imine skeleton of the covalent organic framework material was successfully constructed. Figure 1 .

[0053] In the solid state of covalent organic framework materials 13 In the C CP / MAS NMR spectrum, the characteristic resonance signal of the imine bond at 158 ​​ppm indicates that TPPDA and QA form an imine bond through the Schiff base condensation reaction, and then obtain a covalent organic framework material, such as Figure 2 .

[0054] The crystal structure of the covalent organic framework material was revealed by powder X-ray diffraction (PXRD) test, theoretical simulation and Pawley refinement; the PXRD spectrum of the covalent organic framework material showed a series of peaks at 1.72°, 2.92°, 3.40°, 4.52°, 5.10°, 6.13° and 6.80°, corresponding to (100), (210), (200), (310), (300), (410) and (400) planes, respectively, showing its high cleanliness, such as Figure 3 .

[0055] Record N at 77K 2 Adsorption-desorption isotherms to determine the Kgm topology and permanent porosity of covalent organic frameworks. Figure 4 It can be seen that the covalent organic framework material presents a typical integration of type I and type IV curves, and its specific surface area is large, which is 771m 2 g -1 , the void volume is relatively high, at 1.19 cm 3 g -1 , which is very close to the theoretical value of 1.14 cm based on the structure characterization. 3 g -1 . Significant increase in the low pressure range (P / P 0 <0.1) and obvious hysteresis loops in the medium pressure range demonstrate the hierarchical microporous / mesoporous configuration of the covalent organic framework material; this unique dual-pore property not only facilitates the diffusion of ions but also improves the utilization of redox active sites; in addition, Figure 4 The inset in Figure 2 shows the pore size distribution concentrated around 1.3 nm and 3.4 nm. Figure 4 .

[0056] The invention synthesizes a high-crystallinity imine bond-connected two-dimensional covalent organic framework material composed of a p-type active center and an n-type active center. The material has a kgm topological structure and ordered double-level triangular micropores and hexagonal mesopores. The high crystallinity, high conductivity, unique micropore-mesoporous structure and abundant dual redox active sites of the material enable lithium-ion batteries based on the covalent organic framework material to exhibit high specific capacity, high energy density, high power density and excellent rate performance; in particular, the lithium-ion battery assembled with the covalent organic framework material as the positive electrode has a high specific capacity, high energy density, high power density and excellent rate performance at 10Ag. -1 It has an ultra-long cycle stability of 110,000 cycles at a fast current density and a capacity retention rate of 100%.

[0057] Lithium-ion battery preparation

[0058] The covalent organic framework material, carbon black (Ketjenblacka) and polyvinylidene fluoride (PVDF) binder were dissolved in N-methylpyrrolidone (NMP) to form a viscous slurry, which was cast on aluminum foil and vacuum dried at 85 degrees for 24 hours to obtain a positive electrode sheet. The positive electrode sheet was used as the electrode material. A pure lithium sheet was used as the negative electrode, and 1 molL -1 LiPF 6 EC / EMC=3:7 (v / v) solution was used as the electrolyte, and porous Celgard 2400 was used as the diaphragm. CR2032 button-type batteries were assembled in a glove box with an argon atmosphere (the concentrations of oxygen and water were kept below 1 ppm). Lithium-ion batteries can also be made into button batteries of other models, and lithium-ion batteries can also be batteries of other shapes, such as cylindrical.

[0059] Lithium-ion battery performance test

[0060] The prepared lithium-ion battery was tested on a LAND2001A instrument at 1.2-4.3Vvs.Li / Li + The constant current charge and discharge cycle was carried out within a range of points to test the performance of lithium-ion batteries based on covalent organic framework material electrodes. -1 At a current density of 1.547 W, the capacity retention rate after 110,000 cycles was 100%, showing good cycle stability. Figure 5 .

[0061] The covalent organic framework material of the present invention has excellent electrochemical properties. As a positive electrode material of a lithium ion battery, it has a high specific capacity and outstanding cycle performance, and is a very excellent positive electrode material for a lithium ion battery.

[0062] Parts not described in detail in the present invention belong to common knowledge of those skilled in the art.

[0063] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. An imine bond-connected two-dimensional covalent organic framework material, characterized in that: The structural formula of the covalent organic framework material is:

2. The imine bond-connected two-dimensional covalent organic framework material according to claim 1, characterized in that: The preparation method of the covalent organic framework material comprises the following steps: Step 1: Add 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinolin[2,3-b]acridine-7,14-dione and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine to an o-dichlorobenzene / n-butanol solution and disperse by ultrasonication; Step 2: Add the catalyst and disperse by ultrasonic again to form a uniform system; Step 3, subjecting the system to liquid nitrogen freezing and vacuum degassing treatment; Step 4: Use an alcohol burner to seal the tube under vacuum conditions; Step 5: react at 120 degrees for 72 hours to obtain a crude product; Step 6: Wash the crude product with N,N-dimethylformamide and acetone in sequence, filter it, and dry it in vacuum to obtain a two-dimensional covalent organic framework material.

3. The imine bond-connected two-dimensional covalent organic framework material according to claim 2, characterized in that: In step 1, the volume ratio of o-dichlorobenzene to n-butanol in the o-dichlorobenzene / n-butanol solution is 2:

8.

4. The imine bond-connected two-dimensional covalent organic framework material according to claim 2, characterized in that: The liquid nitrogen freezing and vacuum degassing treatment in step 3 is performed at least 3 times.

5. The imine bond-connected two-dimensional covalent organic framework material according to claim 2, characterized in that: The concentration of the catalyst in step 2 is 6 mol / L acetic acid.

6. The imine bond-connected two-dimensional covalent organic framework material according to claim 2, characterized in that: The structural formula of the 5,12-bis(4-(5,5-dimethyl-1,3-dioxane-2-yl)phenyl)-5,12-dihydroquinoline[2,3-b]acridine-7,14-dione is as follows:

7. The imine bond-connected two-dimensional covalent organic framework material according to claim 2, characterized in that: The structural formula of the N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine is as follows:

8. The imine bond-connected two-dimensional covalent organic framework material according to claim 1, characterized in that: The reaction formula of the preparation method of the covalent organic framework material is as follows:

9. An electrode material, characterized in that: The invention comprises the imine bond-connected two-dimensional covalent organic framework material according to any one of claims 1 to 8.

10. Use of the electrode material according to claim 9 in lithium ion batteries.

Citation Information

Patent Citations

  • Retarded acid system

    CN110564398A

  • Double-active-site covalent organic framework material as well as preparation method and application thereof

    CN116813857A

  • Covalent organic framework polymer electrode material and application thereof in lithium ion total battery

    CN118185005A